The development of intra-individual variability in academic writing: A study on lexical diversity and lexical sophistication - Muzakki Bashori (Universitas Syiah Kuala, 2021)
This study is aimed at finding out (1) whether Lexical Diversity (LD) and Lexical Sophistication (LS) can provide useful insights into the development of academic writing by tracing the interaction between the intra-individual variability in relation to a Dynamic Systems perspective, and (2) whether the supportive interaction between LD and LS can be recognized from the writing development. Twelve academic writing samples written over a 5-year period (2010-2015) by an Indonesian learner of English were employed as longitudinal data. Several tools designed by van Geert and van Dijk (2002), Peltier (2009), and Steinkrauss (2016) were used to analyze the dynamic patterns of language development. The results showed that the development of intra-individual variability in academic writing is in line with the Dynamic Systems Theory as it indicates that the developmental process between the two growers is complex, non-linear, self-organized, unpredictable, revealing attractor states, and constantly changing. The supportive growth movement emerges as the result of the interaction between variables. Finally, it can be concluded that variability is a source of development. Learners might need to be aware of their unique learning trajectory in order to maintain a more stable linguistic development.